Research of aggression in the relationship among athletes in figure skating and their coaches - Zilkova Hrazska, G. (Journal of Human Sport & Exercise, 2012)
In this article, the author writes about problems of the occurrence of aggressive behaviour in interpersonal relations of figure skaters and their coaches. This study of the issue is a part of research in the forthcoming dissertation. In this study, the author investigates the frequency of verbal and physical aggression of coaches against skaters during their training sessions and looks at the connection between the application of authoritative approach in sports training and manifestation of aggressive behaviour of coaches towards athletes during these conflicts.